Design Space and Performance Atlas of a New Type Shaper Mechanism - Wang Bing; Fang Yuefa (Jixie chuandong)
A new type of shaper is proposed,a parallel 2-DOF diamond mechanism is adopted in the new mechanism to convert the input of two servomotors into the single high-power output of the ram,the uniform cutting operation is realized,the processing quality is improved and has industrial valve. The kinematics of the shaper is analyzed and the design space of the main motion mechanism is established. Based on the above,the atlas for ram stroke,velocity,payload capability,stiffness and acceleration are plotted and the relationship between the performance and the link lengths of the mechanism is established. The atlases are very useful for performance evaluation and optimum design for the shaper.